ESP PRACTITIONERS’ ROLE AND THEIR ETHNOGRAPHY: A CASE STUDY OF ESP PRACTITIONERS AT THE INDONESIAN TERTIARY LEVEL - Muhrofi-Gunadi, Kun Aniroh (International Journal of Education, 2016)
This current research aims at revealing factual ESP practitioners’ roles at the tertiary level of education in Malang City, Indonesia. Data were collected through semi-structured interviews and a survey using questionnaires involving 22 ESP practitioners selected randomly from several universities and colleges in Malang. To collect data on the roles of ESP practitioners, the present study adopted two sources in the questionnaires: First, the roles of ESP instructors as teachers, course designers, materials providers, researchers, and evaluators as proposed by Dudley-Evans and St. John (1998), and secondly as a practitioner who has intercultural competence and professional activity competence as defined by Luka (2004) and ethnography (Wall, 2014). The findings showed that the majority (70%) of ESP practitioners realized their roles and some (30%) claimed to learn more on mastering contents, providing materials, conducting research on needs analysis, learning intercultural competence, and realizing the needs to have experiences in industries or related work places of the students. Concerning their ethnography, the majority of ESP practitioners did not have the opportunity to teach, to have internship, and to work in industries. Only 2 (9.1%) ESP practitioners studied the field of what students learn. Future research on the collaboration between academics and practitioners is needed to make ESP classrooms a ‘real world’.